ELEMENTARY SULFUR IN WATERS OF THE BLACK SEA - Volkov I.J. (My University, 1990)
There are no data on the concentrations of elementary sulfur in Black Sea waters, and the nature of its distribution is still undetermined. In order to study elementary sulfur in the waters of the Black Sea, we developed a procedure, in which hydrogen sulfide, elementary sulfur, and combined thiosulfate and sulfide are determined in a single water sample. Thus, S0 was separated from the water by precipitating it (together with H2S) on a suspension of basic zinc carbonate, which is customarily used to separate H2S from S2O32-, as well as from SO42-. The data indicate that the concentration of S0 in the upper part of the hydrogen sulfide zone, to a depth of 200 m, varies widely, from nominal zero (detection threshold 1 to 2 μg/liter) to a maximum measured value of 173 mg/liter (>5 μm-atom/liter), and that the mean concentration in the 150 to 180 m layer falls in the rather narrow interval of 12 to 17 μg-atom/liter. Considerable fluctuation in the S0 content also occur at greater depths, but both the minimum and the mean values at certain depths show a clear trend of increasing concentration of S0 with depth (on average, to about 100 μm/liter at a depth of 2000 m).